How can intercultural school development succeed? The perspective of teachers and teacher educators. (3rd April 2017) - Kiel, Ewald; Syring, Marcus; Weiss, Sabine
Abstract: The large number of newly arrived individuals from other countries, particularly of young people, has had an enormous impact on the school system in Germany. The present study investigated requirements for successful intercultural school development. The study used investigative group discussions, where the groups were composed of teachers and teacher education experts, to identify the structures, measures, attitudes and cooperation required for intercultural school development process. Conditions for success were derived from the qualitative content analysis of these discussions. These conditions address different school levels (e.g. structural, personal or social levels). It was found that intercultural school development cannot be successful without additional resources, as well as further training over the longer term. Solutions for existing language barriers that affect teachers, pupils and parents require structural measures.